Checklist of spiders in Sungai Dusun Wildlife Reserve, Selangor, Malaysia - Chooi, Y. S.; Lau, Wei Hong (Department of Wildlife and National Parks (DWNP) Peninsular Malaysia, 2014)
Sungai Dusun Wildlife Reserve, Selangor was established since 1964. It comprises an area of 4,330 hectares. It is considered one of the important biodiversity hotspots and also the first reserved area to protect Sumatran Rhinos. A study of the biodiversity of spider was carried out during the Biodiversity Inventory Program at Sungai Dusun Wildlife Reserve, Selangor from 26th to 31st October 2009. Samples were collected at selected area. Throughout the program a total of 89 spiders were collected. Among them, spiders from the family Agelenidae, Araneidae, Lycosidae, Oxyopidae, Pisauridae, Salticidae, Sparassidae and Tetragnathidae were recorded. Members of Lycosidae and Araneidae were easily spotted in this area.